Colorectal surgery in octogenarian patients: is it safe? - Cayci, Haci Murat; Erdogdu, Umut Eren; Turkoglu, Mehmet Akif; Orman, Suleyman; Cantay, Hasan; Dilektasli, Evren (The European Research Journal, 2017)
Objectives. The aim of this study was to evaluate the efficiency and safety of resection for colorectal malignancy in elderly patients, by comparing the data from octogenarian (80+ years) patients with other patients of different ages undergoing this procedure. Methods. Data from 80 patients who underwent elective surgery for colorectal malignancy,by a single surgeon in the same center between the dates of May 2013 and May 2015, were evaluated retrospectively. For comparison purposes, patients were classified into three age groups: 65 years and under; between the ages of 66 and 79; and 80+ years old. Demographic features; the presence of comorbidity; colon tumor location; permeation features during colonoscopy; resection type and method; morbidity and mortality; lymph node metastasis and stage of the disease; follow-up period; recurrence during follow-up; and survival data of the patients were recorded and evaluated. Results. Statistically, no significant difference was detected between the three age groups in terms of demographic features; presence of comorbidity; colon tumor location; permeation features in colonoscopy; resection type and method; morbidity and mortality; lymph node metastasis and stage of the disease; follow-up period; recurrence during follow-up; or survival data. Conclusion. Curative resections for colorectal cancer can be safely carried out in octogenarian patients.